COMPUTER MODELING AS ONE OF CONTEMPORARY METHODS OF FORECASTING IN PHARMACEUTICAL TECHNOLOGY - S. O. Losenkova; A. V. Pogrebnyak; Yu. A. Morozov; E. F. Stepanova (Фармация и фармакология (Пятигорск))
The work presents researches devoted to the forecasting of compatibility of additive and drug substances with a method of computer modeling for its use in composition elaboration and technology of transdermal therapeutic systems.